LEKSIKON NAMA TUMBUHAN DALAM PERIBAHASA MASYARAKAT MELAYU SEKADAU - Yulyasa, Resti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstrackResearch in this study focused the observation on cultural objects, namely proverbs. The proverb in question is a proverb that uses the lexicon of a name or part of a plant by Malay Sekadau community. The data was collected in Belitang 1, Belitang sub-district, Sekadau district. Researchers used qualitative methods and used an ethnolinguistic approach in their research. The analysisof the data collected is analyzing the lexical meanings, methaporical meanings, and the function of the Malay Sekadau community proverb. Based on the research conducted, the researchers succeeded in collecting 27 lexicon of the name/part of the plant in the proverbs of the Malay Sekadau community based on the classification (1) the name/part of the plant, while the classification (2) based on the topic of the proverb discussion, the researchers managed to collect 37 topics of discussion. Researchers managed to collect 4 functions of proverb in the society of Malay Sekadau. The number of proverbs that successfull researchers collect, namely 48 the number of proverbs (maxim:12, parable:32, phrase:4). Keywords: proverbs, ethnolinguistic, lexicon of plant names